2020
DOI: 10.1111/nph.16561
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive regulation of virulence genes by microRNA‐like RNAs in Valsa mali

Abstract: Summary MicroRNAs play important roles in the regulation of gene expression in plants and animals. However, little information is known about the action mechanism and function of fungal microRNA‐like RNAs (milRNAs). In this study, combining deep sequencing, molecular and histological assays, milRNAs and their targets in the phytopathogenic fungus Valsa mali were isolated and identified. A critical milRNA, Vm‐milR16, was identified to adaptively regulate the expression of virulence genes. Fourteen isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 69 publications
2
44
0
Order By: Relevance
“…In pathogenic fungi, many virulence genes have been predicted and confirmed to be regulated by sRNAs (Gowda et al, 2010;Guo et al, 2019;Jin et al, 2019;Raman et al, 2017;Xu et al, 2020). We also found that many virulence genes of V. mali could be regulated by milRNAs (Xu et al, 2020). In this study, VmGP, as an important virulence gene, was further demonstrated to be regulated F I G U R E 7 Deletion of VmGP reduces the pathogenicity of Valsa mali.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In pathogenic fungi, many virulence genes have been predicted and confirmed to be regulated by sRNAs (Gowda et al, 2010;Guo et al, 2019;Jin et al, 2019;Raman et al, 2017;Xu et al, 2020). We also found that many virulence genes of V. mali could be regulated by milRNAs (Xu et al, 2020). In this study, VmGP, as an important virulence gene, was further demonstrated to be regulated F I G U R E 7 Deletion of VmGP reduces the pathogenicity of Valsa mali.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, we speculated that Vm-milR37 may play an important role in vegetative growth and pathogenicity. To analyse the function of miRNAs or mil-RNAs, overexpression is an important and widely used method (Jin et al, 2019;Li et al, 2013;Xu et al, 2020). Based on overexpression of Vm-milR37 and pathogenicity assays, Vm-milR37 was confirmed to be involved in the pathogenicity of V. mali.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, monitoring pathogenic modes becomes a necessary preventative step in management of canker disease. Decoding genome sequences (Yin et al 2015) and identifying genes associated with virulence and pathogenicity of the pathogens (Li et al 2015;Song et al 2017;Feng et al 2017aFeng et al , 2017bWu et al 2018;Nie et al 2019;Zhang et al 2019;Xu et al 2020), as well as molecules involved in immunological response of hosts (Feng et al 2017c) will contribute to innovative strategies for management of apple Valsa canker in the future.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%